Equipment Relationship And Supervision Of Refill Drinking Water Depot Processingwith The Presence Of E-Coli In Muko-Muko District - Jaya, Donal; Wulandari, Wulandari; Darmawansyah, Darmawansyah (Universitas Dehasen Bengkulu, 2024)
WHO data shows that around 13 million people were infected from drinking water refills infected with E-Coli bacteria. The data in Indonesia shows that 19.7% of drinking water depots do not meet the requirements contain E-Coli. In Bengkulu Province, there were 48 depots that did not meet the requirements containing E-Coli. In Muko-Muko Regency, E-Coli bacteria were found in 24 depots. The aim of the research is to know the relationship between the equipment and monitoring of refill drinking water depot processing and the existence of E-coli in Mukomuko Regency. This research is a quantitative study using a cross sectional study design. The number of samples in the research were 64 respondents. The analysis used was univariate and bivariate analysis with chi-square test. The results showed that a small portion of the depot identified as E-Coli was 6.2%, a small portion of the depot that was not supervised was 6.2%, a small portion of the depot equipment did not meet the requirements of 9.4%. There is a significant relationship between depot equipment and the presence of E-Coli (p = 0.002), there is no significant relationship between the supervision of refill drinking water depot processing and the presence of E-Coli in Muko-Muko Regency (p = 0.233). It is hoped that the further research will be able to look at other risk factors using multivariate analysis.